Bypaths in Dixie: Folk Tales of the South - Cocke, Sarah Johnson, 1865-1944 (Salt Lake City, UT : Project Gutenberg, 2012)
"Bypaths in Dixie: Folk Tales of the South" by Sarah Johnson Cocke is a collection of folk tales written in the early 20th century. The book captures the charm and humor of Southern life through its storytelling, showcasing the rich tapestry of cultural heritage and oral traditions. It features narratives filled with lively and colorful characters, such as the wise old nurse Mammy Phyllis, who imparts wisdom and playful stories to the children in her care. The opening of the collection introduces readers to the playful and imaginative world of young Willis and his companion Mary Van, who are guided by Mammy Phyllis. Through their interactions and exchanges, particularly regarding a "telephone" made of a table and a rooster's crowing, readers are drawn into a delightful blend of innocence and Southern dialect. This whimsical scenario not only highlights the children's playful nature but also sets the tone for the tales to follow, steeped in folklore, imaginative play, and the nurturing wisdom of older generations. (This is an automatically generated summary.)
The rooster telephone -- Old man Gully's hant -- Jack O'Lantern and the glow worm -- Miss Race Hoss an' de fleas -- Miss Race Hoss's party -- Ned Dog and Billy Goat -- How the billy goat lost his tail -- Shoo fly -- Election day -- Mister Bad 'Simmon Tree -- Big Eye Buzzard -- Miss Lilly Dove -- Mister Grab-All Spider -- Mister Rattlesnake -- Miss Queen Bee -- Mister Tall Pine's Christmas tree -- An afterword.
Release date is 2012-12-10
E-text prepared by the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Short stories; Southern States -- Fiction; African Americans -- Folklore; Tales -- Southern States